2010
DOI: 10.1080/01942620903579393
|View full text |Cite
|
Sign up to set email alerts
|

E-book Usage in Pure and Applied Sciences

Abstract: University of Oklahoma librarians invited faculty in the pure and applied sciences to discuss current and potential e-book use in research and instruction. The study consisted of an online survey followed by individual interviews featuring e-book demonstrations. Faculty viewed e-book titles on a variety of platforms.Opinions were solicited on current publisher or aggregator interfaces, essential and desirable features or functionalities in platforms, and the future of the e-book in academia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Woody, Daniel, and Baker (), in a survey of 91 students, found that participants who had previously used e‐books preferred print texts for learning. Bierman, Ortega, and Rupp‐Serrana (), in a qualitative study of pure and applied science academics, found no significant difference in the way that e‐books were utilized. Respondents indicated that convenience is a significant driver and that e‐books should emulate the functionality of the World Wide Web (e.g., readability, minimum scrolling and clicking, integration of multimedia, hyperlinking, consistency in look‐and‐feel, ability to manipulate and print text and graphics).…”
Section: Introductionmentioning
confidence: 99%
“…Woody, Daniel, and Baker (), in a survey of 91 students, found that participants who had previously used e‐books preferred print texts for learning. Bierman, Ortega, and Rupp‐Serrana (), in a qualitative study of pure and applied science academics, found no significant difference in the way that e‐books were utilized. Respondents indicated that convenience is a significant driver and that e‐books should emulate the functionality of the World Wide Web (e.g., readability, minimum scrolling and clicking, integration of multimedia, hyperlinking, consistency in look‐and‐feel, ability to manipulate and print text and graphics).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers (eg, Bierman, Ortega & Rupp‐Serrano, ; Woody, Daniel & Baker, ) have examined how the students use e‐books in academic contexts. Liu () stated that more studies on the reading behaviors that occur in a digital environment are needed for students, and further empirical research that identifies these behaviors from the reading process is crucial before more extensive use of e‐books is made in educational contexts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wood () reported that the use of e‐books is associated with gains in rhyme detection ability among beginning readers. Shuker and Terreni () also claimed that e‐books could engage young children in new literacy and language learning practices, although some studies have reported that both teachers and students still prefer learning with printed books (Bierman, Ortega, & Rupp‐Serrano ; Woody, Daniel, & Baker ). Based on these results, current e‐books do not yet appear to be ideally suited for learning, with Li, Chen, and Yang () noting one notable problem being that readers cannot construct an effective cognitive map because of the lack of contextual information cues and ineffective navigational mechanisms in e‐books, which means that they have greater difficulty reading on screen than on paper.…”
Section: Introductionmentioning
confidence: 99%